Pulmonary delivery of therapeutic compounds for treating CNS disorders. (September 2011) - Noymer, Peter; Biondi, Sherri; Myers, Dan; Cassella, James
Delivering therapeutic compounds via the lungs presents potential advantages relative to other routes of administration. Depending on the compound and the disease state, these advantages may include: non-invasive medication delivery, ease of administration, higher bioavailability leading to dose sparing and lower systemic toxicity, potentially greater blood–brain barrier penetration and rapid pharmacodynamic effect. The practice of inhaling drugs has been around for centuries, including both medical and recreational usage. It is only more recently that formal clinical development programs have been undertaken specifically to use medication delivery via the lung to achieve systemic blood levels for the treatment of CNS disorders. At present, there are several CNS therapies being developed for pulmonary administration, with some of those programs at or near the marketing authorization stage. While there are still regulatory hurdles before these therapies can be put into practice, the success of these programs thus far demonstrates the scientific viability of inhalation therapies for treating CNS disorders.